2022
DOI: 10.56890/jpacd.v24i.487
|View full text |Cite
|
Sign up to set email alerts
|

Dactylopius opuntiae Cockerell (Hemiptera: Dactylopiidae), an emerging global threat for Opuntia spp: a bibliometric analysis

Abstract: Dactylopius opuntiae Cockerell (Hemiptera: Dactylopiidae) is a worldwide successful biological control agent for some invasive Opuntia Mill. (Caryophyllales: Cactaceae) species, and a primary pest where this species is commercially cultivated, which has renewed its scientific interest. Therefore, this research characterized regularities of the scientific production and identified emerging research trends on D. opuntiae, using one-dimensional and multidimensional bibliometric indicators. The search and retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…Because of the damages caused by D. opuntiae on Opuntia spp., particularly in Brazil and more recently in northern Africa and the Middle East, the scientific production about the methods to combat this pest has increased during the last 15 years. In a recent study, Méndez-Gallegos and Bravo-Vinaja (2022) found out that during the last decade more than 50 % of the scientific production related to D. opuntiae was focused on the application of tactics for its control, this was considered important to identify the types of control tactics that have been carried out to date to focus future lines of research.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the damages caused by D. opuntiae on Opuntia spp., particularly in Brazil and more recently in northern Africa and the Middle East, the scientific production about the methods to combat this pest has increased during the last 15 years. In a recent study, Méndez-Gallegos and Bravo-Vinaja (2022) found out that during the last decade more than 50 % of the scientific production related to D. opuntiae was focused on the application of tactics for its control, this was considered important to identify the types of control tactics that have been carried out to date to focus future lines of research.…”
Section: Introductionmentioning
confidence: 99%